The use of digital materials in physical education lessons for students assigned to a special medical group - Grigan S.A. ,; Butenko T.V. ,; Nagornykh V.N. ,; Tokarev G.N. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is aimedatstudying the potentialandmethods of usingITin the process of organizingphysicaleducationlessonsforstudentsassignedto a specialmedicalgroup. Methods and structure of the study.Methodologyandorganization of the research.Initially, a review of scientificpublicationsandpedagogicalpracticesrelated to the formatsandtypes of educationalactivities of SMGstudents,aswell as informationtechnologytoolsthatcanbeeffectivelyintegratedintophysicaleducationclasses, wascarried out.Then a sociologicalsurveywasconductedamong235students of the St.Petersburgbranch of the RANEPAagedfrom18to24years. Results and conclusions. Results and conclusion. It has been established that the introduction of information technologies into the educational process of SMG students makes it possible to combine and combine various types of activities, such as information and educational, recreational and the creation of digital material. During the classes, knowledge, skills and abilities from the field of IT and physical education and sports are integrated, where, in addition to mastering theoretical knowledge, students gain skills in creating digital content, developing training plans and performing sets of exercises aimed at developing physical fitness and maintaining a healthy lifestyle.